Dampak Penyebaran Hadis Lemah dan Palsu dalam Tatanan Kehidupan Bermasyarakat (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2020)
Abstract Hadith is the source of the second law of Islam. To be functioned as bayan (explanatory) of the Qur'an and at the same time as a guideline, he must undergo a selection process called hadith keshahihan test or hadith criticism test. This neglect of critical attitudes in turn causes the number of hadiths dhaif (weak hadith) and hadith mawdhu ' (false hadith) spread in the community. Among the groups responsible for the spread of these hadiths are the da'i (khatib and muballigh) who do not equip themselves with adequate mastery of hadith science, where they tend to cite hadiths not from the original sources (the book of hadith mu'tabar). In turn, the result of the phenomenon of the spread of hadith dhaif and mawdhu' itself is the spread of heresy behavior and neglect of the Sunnah of the Prophet. Keywords: Authentication of Hadith, Hadith Dhaif, Hadith Mawdhu' Abstrak Hadis adalah sumber hukum kedua agama Islam. Untuk dapat difungsikan sebagai bayan (penjelas) al-Qur’an dan sekaligus sebagai pedoman, ia harus menjalani proses seleksi yang disebut dengan uji keshahihan hadis atau uji kritik hadis. Pengabaian terhadap sikap kritis inilah yang pada gilirannya menyebabkan banyaknya hadis dhaif (hadis lemah) dan hadis mawdhu’ (hadis palsu) tersebar di tengah masyarakat. Di antara kelompok yang bertanggung jawab terhadap penyebaran hadis-hadis ini adalah para da’i (khatib dan muballigh) yang tidak melengkapi diri dengan penguasaan ilmu hadis yang memadai, dimana mereka cenderung mengutip hadis tidak dari sumber-sumber aslinya (kitab hadis mu’tabar). Pada gilirannya, akibat dari fenomena penyebaran hadis dhaif dan mawdhu’ sendiri adalah merebaknya perilaku bid’ah dan pengabaian sunnah Nabi. Keywords: Uji Keshahihan Hadis, Hadis Dhaif, Hadis Mawdhu’